1992
DOI: 10.1104/pp.98.2.694
|View full text |Cite
|
Sign up to set email alerts
|

Photosynthesis and Photorespiration in Presenescent, Senescent, and Rejuvenated Soybean Cotyledons

Abstract: Various growth and physiological parameters were measured in germinating, presenescent, and senescing soybean (Glycine max [L.] Merr.) cotyledons and in cotyledons rejuvenated by epicotyl removal 18 days after planting. The maximal measured carbon dioxide exchange rates (CER) in the cotyledons were in the range of those reported for field-grown soybean leaves. Rejuvenated cotyledons accumulated total chlorophyll in excess of the maximum observed in presenescent cotyledons. When photosynthetic rates were expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
19
0
1

Year Published

1998
1998
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 13 publications
4
19
0
1
Order By: Relevance
“…Because cotyledons are autotrophic organs (Marek and Stewart, 1992), Ser will most likely be synthesized via photorespiration and transported to the SAM via the phloem. Taken together, Ser synthesized by either photorespiration or PS pathway is essential for proper leaf development in plants.…”
Section: Figure 11 (Continued)mentioning
confidence: 99%
“…Because cotyledons are autotrophic organs (Marek and Stewart, 1992), Ser will most likely be synthesized via photorespiration and transported to the SAM via the phloem. Taken together, Ser synthesized by either photorespiration or PS pathway is essential for proper leaf development in plants.…”
Section: Figure 11 (Continued)mentioning
confidence: 99%
“…It is reported that soybean cotyledons senesce and fall off when the third trifoliate leaf unfolds (Peterman and Siedow, 1985;Harris et al, 1986;Marek and Stewart, 1992). There may be varietal differences in this characteristic.…”
Section: Discussionmentioning
confidence: 99%
“…In soybean, the green cotyledons play an important role after emergence because the cotyledons not only have a storage-mobilizing function but also assimilate energy through photosynthesis (Harris et al, 1986;Brown and Huber, 1987;Marek and Stewart, 1992;Ramana et al, 2003;Kitajima, 2003;Hanley and May, 2006;Zhang et al, 2008). Zheng et al (2011) insisted that the cotyledons provide a major proportion of the assimilation needed for seedling growth until the first true leaf becomes a significant exporter of photosynthate.…”
mentioning
confidence: 99%
“…Decapitation of the shoot above differentiated leaves or the entire epicotyl above the yellow cotyledons, thus leading to subsequent rejuvenation is an approach for studying reversibility of the senescence process (Van Staden and Carmi 1982;Marek and Stewart 1992;Ananieva et al 2004). Cotyledon natural senescence and rejuvenation have not been sufficiently studied (Biswal and Biswal 1984;Marek and Stewart 1992;La Rocca et al 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Cotyledon natural senescence and rejuvenation have not been sufficiently studied (Biswal and Biswal 1984;Marek and Stewart 1992;La Rocca et al 1996). Changes in CO 2 exchange rates, Rubisco levels and photorespiration were reported for presenescent, senescing and rejuvenated soybean cotyledons (Marek and Stewart 1992).…”
Section: Introductionmentioning
confidence: 99%